Parameters influencing maturation of female marine polychaete Perineris nuntia (Savigny , 1818) in Southern Iloilo. - Maceren, Mercedes D. (College of Fisheries, University of the Philippines in the Visayas, 2010)
Female marine polychaetePerimerisnuntia were collected from the intertidal area of Guimbal, Iloilo, Philippines from June to November 2009 to determine the relationship between total length (TL) and body weight (BW), fecundity and BW, and the influence of lunar cycle and smapling months on oocyte size-frequency distribution and maturation stages. The relationship between total length and body weight of the female P. nuntia was found to be best described as BW = 0.0016TL2.0052. Total length ranged from 11-30 cm with the size range 21-25 cm dominating in all the sampling months. Fecundity and BW relationship was highly significant (F = 36.991 + 83.127BW). The average fecundity was 20,963 oocytes/g female. The maturation stages based on size and histology of oocytes were established as immature (Stage 1), maturing (Stage II), mature (Stage III), ripe (stage IV) and spent (Stage V). Corresponding changes in body color and parapodial morphology were also described. The pattern of oocyte development in P. nuntia included a phase when oocytes were heterogeneous (<173 um) and became more uniform in size (>173 um) when approaching the final stage of development. Four size groups of oocytes were observed in P. nuntia : <100 um, 101-140 um, 141-180 um and 181-220 um. The absence of 181-220 um size during new moon in all sampling months and in July-September that spawning might have occurred during these periods. Sampling months significantly influenced female maturation stages.